SURVEY ASSESSMENT OF INDIGENOUS KNOWLEDGE FOR SEEDS CONSUMPTION OF SWEET BASIL AND PSYLLIUM BY LOCAL COMMUNITY IN SOUTHERN PUNJAB, PAKISTAN - Rehana KHALIQ; Ovidiu TITA; Camelia SAVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The assessment of indigenous knowledge for seeds consumption of sweet basil and psyllium as a source of fiber by local community was carried out in different parts of southern Punjab, Pakistan. A structured questionnaire was prepared with close ended questions. Data collected were subjected to the descriptive statistic like percentage, frequency, bar and pie chart. According to the findings of surveyed analysis we concluded that 77 % people under surveyed attained the traditional knowledge about sweet basil and psyllium from family members whereas results showed that most of the people (87.50 %) who used these plants as a source of fiber were above age of 40. The study further revealed that people of local community consumed the seeds of selected plants only based on traditional knowledge and reluctant to used them more frequently. Most of the surveyed people (87.5%) used Psyllium as a source of fibers to cure the digestive problems whereas sweet basil seeds used by the people (44 %) only for seasonal recreational purposes without knowing its specific worth of efficacy. On the other hand, majority of respondent preferred to use whole grains as compared to refined grains. From these results we found clear idea for novel food product preparations in future study from seeds of selected medicinal plants in according to the needs of consumers.